Saúde bucal nas escolas: relato de experiência - Santos, Karina Tonini dos [UNESP]; Garbin, Artênio José Isper [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (My University, 2012)
The need for a closer contact between students and the community reality, as well as, the necessity of providing an education that can result in social changes early in life were crucial for the development of the Extension Project : Oral Health Education, which was developed in Public Child Care Schools in Araçatuba. The aim of this article is to describe the project, emphasizing its educational aspects and to share this experience in order to allow for reflection about this practice.

La necesidad de acercar a los académicos a la realidad experimentada por la comunidad, así como la de educar a los que buscan la transformación social, desde una edad temprana ha dado lugar al desarrollo de Proyecto de Extensión de la salud oral de Educación, celebrada en las Escuelas Municipales de Educación Infantil en Araçatuba. El propósito de este artículo es describir el proyecto, haciendo hincapié en los aspectos educativos con el fin de compartir esta experiencia y reflexionar sobre la práctica.

A necessidade de aproximação entre acadêmicos e a realidade vivenciada pela comunidade, bem como a de educar buscando a transformação social, desde uma tenra idade, levaram ao desenvolvimento do Projeto de Extensão de Educação em Saúde Bucal, realizado nas Escolas Municipais de Educação Infantil de Araçatuba. A proposta do artigo é descrever o projeto, enfatizando os aspectos educativos, a fim de compartilhar essa experiência e refletir sobre a prática.
Oral health in schools: experience report
La salud bucal en las escuelas: un relato de experiencia
Keywords: Programas educativos; Saúde bucal; Educação em saúde; Programas de educación; Salud bucal; Educación para la salud; Programas educativos; Saúde bucal; Educação em saúde